Apocalypse . . . Eventually: Trans-Corporeality and Slow Horror in M. R. Carey’s The Girl with All the Gifts - Druzak, Courtney A. (Text Matters: A Journal of Literature, Theory and Culture, 2022)
This article examines M. R. Carey’s 2014 zombie apocalypse novel The Girl with All the Gifts through the ecofeminist concept of trans-corporeality as defined by Stacy Alaimo in Bodily Natures. Carey’s heroine Melanie showcases how humans can re-conceptualize their relationship to a more-than-human, or natural, world that is both exterior to the self and always-already a part of the self through fungal agency. Indeed, the novel continuously engages in intimate human-environment interconnections that, in their horrific capacities, are meant to inspire readers to reflect upon their own enmeshment in a larger, material world. The novel’s use of the real fungus Ophiocordyceps as the more-than-human agent that inspires the transformation of humans into zombies provides a vision for how humans can more ethically relate, in posthuman manners, to a more-than-human world. Finally, this article considers the novel as a depiction of slow horror, or a gradual descent into apocalypse.